2017
DOI: 10.1021/acs.macromol.6b02691
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Hydrogels via Carbon Nitride Initiated Polymerization

Abstract: The utilization of graphitic carbon nitride (g-CN) as photoinitiator for hydrogel formation is reported. On top of the photochemical activity, g-CN entails the role of a reinforcing agent. Hydrogels formed via g-CN (0.6 wt % g-CN and 11 wt % solid content in total) possess significantly increased mechanical strength, around 32 times stronger storage moduli (from 250 Pa for the reference sample up to 8300 Pa for g-CN derived hydrogels) than the ones initiated with common radical initiators. In addition, the g-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 51 publications
1
71
0
7
Order By: Relevance
“…Reversible assembly of g‐CN particles in water was shown to provide hydrogel‐like 3D networks, presenting dye absorption and degradation platforms . Recently, it was employed in polymer chemistry to perform photopolymerization or fabricate hydrogels . It was shown that g‐CN sheets act as reinforcer and photoinitiator in radical mediated hydrogel formation with surface charge being one of the important parameters regarding hydrogel strength .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reversible assembly of g‐CN particles in water was shown to provide hydrogel‐like 3D networks, presenting dye absorption and degradation platforms . Recently, it was employed in polymer chemistry to perform photopolymerization or fabricate hydrogels . It was shown that g‐CN sheets act as reinforcer and photoinitiator in radical mediated hydrogel formation with surface charge being one of the important parameters regarding hydrogel strength .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was employed in polymer chemistry to perform photopolymerization or fabricate hydrogels . It was shown that g‐CN sheets act as reinforcer and photoinitiator in radical mediated hydrogel formation with surface charge being one of the important parameters regarding hydrogel strength . Our group recently developed a one pot grafting method to anchor functional groups on the surface of g‐CN, showing excellent dispersions in aqueous and organic media .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, graphitic carbon nitride (g‐C 3 N 4 ) as metal‐free semiconductor has attracted extensive attention . It has been successfully used to reinforce hydrogels, and meanwhile bestowed additional properties on the obtained composite hydrogels . Nevertheless, the current synthetic process is relatively complex and needs external initiators or cross‐linkers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to preserve the completely hydrophilic self-assemblies crosslinking in aqueous solution is a valid option as it has been utilized frequently in nano particle 29,30 and hydrogel formation. 31,32 In the case of DHBC-based systems crosslinking has been performed with self-assemblies from PEO-b-poly(N-vinylpyrrolidone) (PEO-b-PVP) 33 and PEO-b-PEtOx. 34 A bio-derived building block that has proven to be useful in DHBC self-assembly so far is Pull, 20,21 which is a linear nonionic poly(saccharide) consisting of α-1,6-linked maltotriose units.…”
Section: Introductionmentioning
confidence: 99%